A Two‐Terminal Optoelectronic Synapses Array Based on the ZnO/Al2O3/CdS Heterojunction with Strain‐Modulated Synaptic Weight. (12th February 2023) - Han, Xun; Zhang, Yufei; Huo, Zhihao; Wang, Xiandi; Hu, Guofeng; Xu, Zhangsheng; Lu, Hui; Lu, Qiuchun; Sun, Xidi; Qiu, Li; Yan, Peiguang; Pan, Caofeng
Abstract: Artificial optoelectronic synapses with flexibly regulated synaptic weight are crucial to the rapidly evolved artificial visual system. Although three‐terminal devices with transistor geometry have exhibited controllable synaptic response through applying electrical pulses on the gate terminal, the complicated device structure limits its integration with array configurations. In this work, a simple two‐terminal optoelectronic synapses array based on the ZnO/Al2 O3 /CdS heterojunction with tunable synaptic weight is presented. It can respond to UV and green light stimulation in a neuromorphic manner, allowing the implementation of the basic synaptic function. By introducing the piezo‐phototronic effect, the synaptic weight can be regulated in multilevels, extending the forgetting time by 30.08% and reducing training epochs for image recognition by 36.13%. In addition, the device can extract the target image from massive noisy optical inputs avoiding redundant data memorization. This work provides a novel method to regulate the synaptic weight of the simple two‐terminal device configuration through the piezo‐phototronic effect, showing potential applications for the mimicry of the human visual‐perception system. Abstract : A two‐terminal artificial optoelectronic synapses array is demonstrated, which is stimulated by both the UV and green light in a neuromorphic manner. With the modulated synaptic weight by the piezo‐phototronic effect, the array demonstrates enhanced functions of image memorization and recognition and the capability of image preprocessing to filter redundant noise data for mimicking the human visual‐perception systems.